Impact of Significant Coronary Artery Calcification Reported on Low-Dose Computed Tomography Lung Cancer Screening. Issue 2 (March 2020) - Mendoza, Dexter P.; Kako, Bashar; Digumarthy, Subba R.; Shepard, Jo-Anne O.; Little, Brent P.
Abstract : Background: Coronary artery calcification (CAC) is a common and important incidental finding in low-dose computed tomography (LDCT) performed for lung cancer screening (LCS). The impact of these incidental findings on patient management is unclear. Purpose: The goals of our study were to determine the impact of reporting CAC on patient management and to determine whether standardized reporting of CAC affects the likelihood of future interventions. Methods: In this IRB-approved retrospective study, we queried our LCS database for reports of LDCT performed between January 2016 and September 2018. All reports with significant findings of CAC designated with the letter "S" for any Lung-RADS category were selected. The grading of CAC was extracted from the reports. Medical records were reviewed for each patient to determine demographics, clinical history, medications, and cardiac-related diagnostic and interventional procedures. The changes in management after the report of significant CAC on LDCT were documented. Statistical analysis with Student t test and Pearson χ 2 test was performed. Results: A total of 756/3110 patients (mean age: 67±6.4 y; M=466, 61.6%: F=290, 38.4%) were reported to have significant CAC on LDCT for LCS. Of them, 236/756 patients (31.2%) had established coronary artery disease (CAD) at baseline, before the initial LDCT. A change in management was observed in 155/756 patients (20.5%). The most common changes in management included the following: alteration in medication regimen (n=114/155, 73.5%), stress testing (n=65/155, 41.9%), and referral to a cardiologist (36/155, 23.2%). Percutaneous coronary intervention (4, 2.6%) and surgery (3, 1.9%) were uncommon. Changes in management were more common in those without established CAD and in those whose CAC was semiquantitatively graded (35% vs. 25%, P =0.02). Conclusion: CAC is a common significant finding in LDCT for LCS. Reporting of CAC in patients with nonestablished CAD and semiquantitative assessment resulted in changes in management. Abstract : Supplemental Digital Content is available in the text.